PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN (STUDY PADA PERUSAHAAN MANUFAKTUR INDUSTRI BARANG KONSUMSI (CONSUMER GOOD INDUSTRY) YANG TERDAFTAR DI BURSA EFEK INDONESEIA PERIODE 2015 - 2018) - Rosmila, Rosmila; Sarita, Buyung; Madi, Riski Amalia; Istianandar, Farhan Ramdhani; Zaluddin, Zaluddin (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to determine the effect of corporate social responsibility on ROA. In addition, to determine the effect of Corporate social responsibility on ROE. And to determine the effect of Corporate social responsibility on stock returns. The type of data is secondary data sourced from the Indonesian stock exchange. The number of samples in this study amounted to 12 samples each of 4 years. The analytical tool used is quantitative descriptive analysis using Eviews 9.Â  The results show that the test in this study explains that the disclosure of corporate social responsibility activities has a positive and significant effect on return on assets. The results of the second test show that there is a negative and insignificant effect of the disclosure of corporate social responsibility on return on equity. The company's profitability can not be measured by the amount of disclosure of social responsibility or from the level of leverage. From the results of the analysis for the third hypothesis with the corporate social responsibility variable on stock returns, it shows a negative effect and there is no significant effect on the corporate social responsibility variable on stock returns.